Curriculum Management in Improving the Quality of Islamic Boarding School Education - Faridatul Jannah; Ali Nurhadi; Faiqotul Munawwarah (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of this study is to find out how the analysis of the management of improving the quality of Islamic boarding schools in the Al-Miftah Dempo Timur Islamic boarding school. This study uses a qualitative field study approach. Data collection techniques using interview, observation and documentation methods. The results of this study indicate that the analysis of improving the quality of Islamic boarding schools includes Identification of the need to improve the quality of Islamic boarding schools, Effective approach methods to find out the Islamic boarding school curriculum in improving the quality of education. The results of this study are the analysis of curriculum management, the scope of the study of Islamic boarding school education curriculum management and the last is the supporting and inhibiting factors of Islamic boarding school curriculum management in improving education.